Southern Beaufort Sea Polar Bear Fatty Acid Data, Spring Samples 2004-2016 ... - U.S. Geological Survey, Alaska Science Center; Jeffrey F Bromaghin; Todd C Atwood; Karyn D Rode (U.S. Geological Survey, 2024)
These data consist of the fatty acid composition (percent of mass) of adipose tissue samples from polar bears in Alaska's southern Beaufort Sea. Fat biopsy samples were collected from polar bears that were either captured or biopsy darted along the north coast of Alaska or on offshore ice during March, April, or May from 2004 to 2016. The data also include an identification code unique to an individual bear, sex, age class, and the date of sample collection. ...